Surrogate warfare : the transformation of war in the twenty-first century - Krieg, Andreas; Rickli, Jean-Marc (Georgetown University Press, 2019)
This phenomenon ranges from arming proxies, to the use of armed drones, to cyber propaganda. Krieg and Rickli bring old, related practices such as war by mercenary or proxy under this new overarching concept. Apart from analyzing the underlying sociopolitical drivers that trigger patrons to substitute or supplement military action, this book looks at the intrinsic trade-offs between substitution and control that shapes the relationship between patron and surrogate. This book will be essential reading for anyone studying contemporary conflict.